2012
DOI: 10.1128/jcm.01368-12
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Easy Identification of Capsular Serotypes of Streptococcus pneumoniae by Use of Fragment Analysis by Automated Fluorescence-Based Capillary Electrophoresis

Abstract: The purpose of this study was to develop a high-throughput method for the identification of pneumococcal capsular types. Multiplex PCR combined with fragment analysis and automated fluorescent capillary electrophoresis (FAF-mPCR) was utilized. Only 11 results were discordant with the Quellung reaction. However, latex reaction and Quellung results of the second reference laboratory agreed with FAF-mPCR for 9 of these 11 strains (82%). Therefore, we considered that only 2 of 394 strains (0.5%) were not properly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 42 publications
(49 reference statements)
0
45
0
Order By: Relevance
“…A high throughput method for the identification of pneumococcal capsular types was established using multiplex PCR-CE (FAF-mPCR) [29]. The automation of the process can genotype 30 isolates in a few hours and carry out 90 reactions in 90 min, three-fold less time than that of Quellung reaction, these results indicated that FAFmPCR was a useful and alternative method to determine the capsular serotype of Streptococcus pneumoniae.…”
Section: Detecting and Diagnosing Bacteriamentioning
confidence: 88%
“…A high throughput method for the identification of pneumococcal capsular types was established using multiplex PCR-CE (FAF-mPCR) [29]. The automation of the process can genotype 30 isolates in a few hours and carry out 90 reactions in 90 min, three-fold less time than that of Quellung reaction, these results indicated that FAFmPCR was a useful and alternative method to determine the capsular serotype of Streptococcus pneumoniae.…”
Section: Detecting and Diagnosing Bacteriamentioning
confidence: 88%
“…DNA detection of pneumolysin ( ply ) and LytA gene by Real-Time PCR ( polymerase chain reaction ) in CSF was performed according to previously reported assays [2124]. …”
Section: Methodsmentioning
confidence: 99%
“…It is based on the use of 40 different primers pairs for the specific detection of 40 serotypes/serogroups and a pair of additional primers for detecting a fragment of the cpsA (wzg) gene, which is highly common to all capsular serotypes. So, this technique allows to detect all capsular types and to differentiate 40 serotypes/ serogroups [13]. On the other hand, in samples with a positive result between 30 and 35 cycles, serotypes were identified by a published multiplex real-time PCR methodology that detects the wzg gene and differentiates 21 serotypes [12].…”
Section: Serotype Identificationmentioning
confidence: 99%